If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12p + -30q + 36 = 0 Reorder the terms: 36 + 12p + -30q = 0 Solving 36 + 12p + -30q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + 12p + -36 + -30q = 0 + -36 Reorder the terms: 36 + -36 + 12p + -30q = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 12p + -30q = 0 + -36 12p + -30q = 0 + -36 Combine like terms: 0 + -36 = -36 12p + -30q = -36 Add '30q' to each side of the equation. 12p + -30q + 30q = -36 + 30q Combine like terms: -30q + 30q = 0 12p + 0 = -36 + 30q 12p = -36 + 30q Divide each side by '12'. p = -3 + 2.5q Simplifying p = -3 + 2.5q
| 2*3.14*r=7.51 | | 7x-9x+6=-4x+6 | | 2a+6b+18c= | | 4/9(18w-36)-2/9(9w/2-9)=0 | | 5(x-1)=3(x+9) | | 32r-80z= | | 30m-120= | | s-15=-33 | | 24v+32w= | | 9p+21= | | 3x+2+5x-5=25 | | 6x+2y+6=0 | | 12x+8=10x+40 | | 10x^3+8x^2+2x=0 | | 9x+6-10x-25=30 | | 12n+2=4n+3 | | -3x+4=(-2)x+(-19) | | 4f-24g= | | 4+12/x=7 | | 12n+5=4n+6 | | -27-3x=6x+24 | | -81-9x=21+8x | | 10r-15s= | | 12n+3=4n-6 | | 9x^2-79x-130=0 | | 14c+28d= | | 7y+6x-3=3y-3x+2 | | n+(-20)=7-n | | 84-3x=3x+24 | | 4y+6z= | | 35-3x=2x | | 61-3x=61-3x |